Neologisms and their evolvement in contemporary Australian English; Язык. Общество. Образование - Аксёнова Н. В. Наталия Валерьевна (Актуальные векторы исследований и подходы в современной лингвистике, 2023)
The Australian English has always been an amazing amalgamation of colourful words and expressions. This paper will delve into some new words that have found their way into Australian vocabulary illustrating the richness and fluidity of Australian English and, mainly, new neologisms connected with different foods will be taken into account in this paper